Community participation for the use of renewable energies in ciudad Ixtepec, Oaxaca (2008-2015) - Wendy Marilú Sánchez-Casanova; Bendreff Desilus (Journal of Risk and Financial Management, 2020)
This paper aims to examine the redefinition of rural actors and practices in the context of the Wind Farm Corridor of the Isthmus of Tehuantepec. That redefinition addresses issues such as the benefits of wind farms, the role of the land in the use of wind energy, requirements for the use of wind, arguments of disagreement with wind farms, manifestations of that disagreement, and the feasibility of community wind farms. Adopting a case study methodology from a qualitative perspective, and "worded" data collected through semi-structured interviews, it was detected that, despite the disapproval of residents of the Oaxacan Isthmus due to a dispossession claimed to the Federal Electricity Commission (Comisión Federal de Electricidad, CFE) and private companies, many of the landowners in Ciudad Ixtepec have decided to become wind entrepreneurs by a community wind farm, facing opposition and mistrust regarding their capacities.
Keywords: 330; new rurality; rural ownership; wind entrepreneurs